Design and Fabrication of New Nanostructured SnO2‐Carbon Composite Microspheres for Fast and Stable Lithium Storage Performance. Issue 16 (20th May 2014) - Ko, You Na; Park, Seung Bin; Kang, Yun Chan
<x xml:space="preserve">Abstract</x> One‐pot method for metal oxide–carbon composite microsphere with three‐dimensional ordered macroporous (3DOM) structure is first introduced. The 3DOM structured SnO2‐carbon microspheres prepared as the first target material show superior electrochemical properties as anode material for lithium ion batteries. The newly developed process can be applied to the preparation of 3DOM‐structured metal oxide–carbon composite microspheres for wide applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>